Agreement of amyloid PET and CSF biomarkers for Alzheimer's disease on Lumipulse. Issue 9 (28th August 2019) - Alcolea, Daniel; Pegueroles, Jordi; Muñoz, Laia; Camacho, Valle; López‐Mora, Diego; Fernández‐León, Alejandro; Le Bastard, Nathalie; Huyck, Els; Nadal, Alicia; Olmedo, Verónica; Sampedro, Frederic; Montal, Victor; et al.
Abstract: Objective: To determine the cutoffs that optimized the agreement between 18 F‐Florbetapir positron emission tomography (PET) and A β 1‐42, A β 1‐40, tTau, pTau and their ratios measured in cerebrospinal fluid (CSF) on the LUMIPULSE G600II instrument, we quantified the levels of these four biomarkers in 94 CSF samples from participants of the Sant Pau Initiative on Neurodegeneration (SPIN cohort) using the Lumipulse G System with available 18 F‐Florbetapir imaging. Methods: Participants had mild cognitive impairment ( n = 35), AD dementia ( n = 12), other dementias or neurodegenerative diseases ( n = 41), or were cognitively normal controls ( n = 6). Levels of A β 1‐42 were standardized to certified reference material. Amyloid scans were assessed visually and through automated quantification. We determined the cutoffs of CSF biomarkers that optimized their agreement with 18 F‐Florbetapir PET and evaluated concordance between markers of the amyloid category. Results: A β 1‐42, tTau and pTau (but not A β 1‐40) and the ratios with A β 1‐42 had good diagnostic agreement with 18 F‐Florbetapir PET. As a marker of amyloid pathology, the A β 1‐42/A β 1‐40 ratio had higher agreement and better correlation with amyloid PET than A β 1‐42 alone. Interpretation: CSF biomarkers measured with the Lumipulse G System show good agreement with amyloid imaging in a clinical setting with heterogeneous presentations of neurological disorders. Combination of A β 1‐42 with A β 1‐40 increases the agreement between markers of amyloid pathology.